2022
DOI: 10.1021/acsestwater.2c00003
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Endogenous SARS-CoV-2 and Pepper Mild Mottle Virus RNA in Wastewater-Settled Solids

Abstract: Limited information is available on the decay rate of endogenous SARS-CoV-2 and pepper mild mottle virus (PMMoV) RNA in wastewater and primary settled solids, potentially limiting an understanding of how transit or holding times within wastewater infrastructure might impact RNA measurements and their relationship to community COVID-19 infections. In this study, primary settled solids samples were collected from two wastewater treatment plants in the San Francisco Bay Area. Samples were thoroughly mixed, aliquo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…Temperature had the strongest effect on SARS-CoV-2 viral concentration (Kendall's tau, p < 0.05), significantly reducing observed concentration exposed to warmer conditions in JI (paired t-test, p = 0.02), and SS (paired t-test, p = 0.046). Temperature posing a significant effect on SARS-CoV-2 decay is consistent with other studies that indicate coronaviruses, and specifically SARS-CoV-2, are sensitive to warmer temperatures [15,[36][37][38][39] where decay rates for similar temperature windows ranged between 0.021-2.16 k/day [15,20,21,39]. Increasing temperatures reduce RNA stability, and make it more difficult for any virus to survive [40].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Temperature had the strongest effect on SARS-CoV-2 viral concentration (Kendall's tau, p < 0.05), significantly reducing observed concentration exposed to warmer conditions in JI (paired t-test, p = 0.02), and SS (paired t-test, p = 0.046). Temperature posing a significant effect on SARS-CoV-2 decay is consistent with other studies that indicate coronaviruses, and specifically SARS-CoV-2, are sensitive to warmer temperatures [15,[36][37][38][39] where decay rates for similar temperature windows ranged between 0.021-2.16 k/day [15,20,21,39]. Increasing temperatures reduce RNA stability, and make it more difficult for any virus to survive [40].…”
Section: Discussionsupporting
confidence: 88%
“…Specific parameters in the sewer collection system that have a known influence on viral RNA and are assumed to have an impact on SARS-CoV-2 detection in wastewater, include pH, temperature, organic matter, solids content, residence time in the sewer, sampling, and microbial antagonism [15][16][17]. While various studies have performed analysis on the decay of SARS-CoV-2 RNA in wastewater influent in a laboratory setting, they are often performed with surrogate enveloped virus spikes [15,[18][19][20][21][22] which have been shown to behave differently than authentic in situ SARS-CoV-2 found within the wastewater matrix [23,24]. A major barrier to performing in situ studies and comparing real wastewater systems is that the true input of SARS-CoV-2 virus from the population is unknown and likely different for individuals depending on the severity of disease, stage of infection, and other factors [25].…”
Section: Introductionmentioning
confidence: 99%
“…Once at the laboratory, the sample was stored at 4 °C and analyzed within a week. Previous work indicated minimal degradation of viral RNA RT-PCR targets during this time frame ( Roldan-Hernandez et al, 2022 ; Yang et al, 2022 ). The autosamplers malfunctioned twice and no sample was available at School A on April 19 and at School B on April 22.…”
Section: Methodsmentioning
confidence: 66%
“…Several studies have demonstrated that SARS-CoV-2 particles could be detected in 2-3 magnitude higher concentrations in solids and sludge of some wastewater samples than in the aqueous phase ( Peccia et al, 2020 ; D'Aoust et al 2021 ; Graham et al, 2021 ; Carillo-Reyes et al 2021 ; Westhaus et al 2021 ; Buonerba et al 2021 ). Roldan-Hernandez et al (2022) have shown persistence of SARS-CoV-2 in solids with a slower rate of decay than in the wastewater influent, further suggesting the importance of including the solid phase which can adsorb the viral particles and RNA. Our results suggest the need for a simple and efficient procedure for concentration of viral particles and RNA from the entire sample.…”
Section: Resultsmentioning
confidence: 99%